High-Performance Schottky Junction for Self-Powered, Ultrafast, Broadband Alternating Current Photodetector - Lim, Jaeseong; Kumar, Mohit; Seo, Hyungtak (Korean Journal of Materials Research, 2022)
In this work, we developed silver nanowires and a silicon based Schottky junction and demonstrated ultrafast broadband photosensing behavior. The current device had a response speed that was ultrafast, with a rising time of 36 μs and a falling time of 382 μs, and it had a high level of repeatability across a broad spectrum of wavelengths (λ = 365 to 940 nm). Furthermore, it exhibited excellent responsivity of 60 mA/W and a significant detectivity of 3.5 × 1012 Jones at a λ = 940 nm with an intensity of 0.2 mW cm-2 under zero bias operating voltage, which reflects a boost of 50%, by using the AC PV effect. This excellent broadband performance was caused by the photon-induced alternative photocurrent effect, which changed the way the optoelectronics work. This innovative approach will open a second door to the potential design of a broadband ultrafast device for use in cutting-edge optoelectronics.
Keywords: Alternating current; Alternating current photovoltaic effect; Performance; Schottky junctions; Self-powered; Self-powering; Self-powering.; Silicon-based; Silver nanowires; Ultra-fast; Alternating current photovoltaic effect; Photodetector; Schottky junction; Self-powering.; Silver nanowire